Positive electrode material and preparation method thereof and secondary battery

By using polyacrylic acid as a carbon source in the lithium manganese iron phosphate positive electrode material and forming a carbon cladding layer through microwave heating, the problem of unstable carbon layer quality is solved and the electrochemical performance of the material is improved.

CN118841555BActive Publication Date: 2025-02-28NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411311186.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-28
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing carbon layer coated with lithium manganese phosphate is unstable in quality, resulting in poor material capacity, low first efficiency and poor long cycle performance.

Method used

By introducing polyacrylic acid as a carbon source into the positive electrode material, its viscosity is controlled between 8000mm2/s~17000mm2/s, and a carbon cladding layer is formed by microwave heating to ensure that the thickness consistency of the carbon layer and the pore distribution meet specific standards.

Benefits of technology

The quality control of the carbon layer is realized, and the compaction density, discharge capacity, first effect and long cycle performance of the cathode material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to the technical field of power batteries, and in particular to a positive electrode material and a preparation method thereof and a secondary battery. The positive electrode material comprises lithium iron manganese phosphate particles and a carbon coating layer coating the lithium iron manganese phosphate particles. The chemical formula of the lithium iron manganese phosphate particles is LiMn x Fe y PO4, wherein x:y=(0.4~0.8):(0.2~0.6), the difference between the maximum and minimum thickness of the carbon coating layer is between 1nm~2nm; and the positive electrode material is distributed with multiple pores, wherein the number of pores with a pore diameter exceeding 50nm accounts for 35%~50% of the total number of pores. The positive electrode material has a high compaction density and is conducive to the preparation of batteries with high discharge capacity and first efficiency and good long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of power batteries, and in particular to a positive electrode material and a preparation method thereof, and a secondary battery. Background Art

[0002] Lithium manganese iron phosphate (LMFP) is a new type of positive electrode material for lithium-ion batteries. It has the same crystal structure as lithium iron phosphate, is safe and low-cost, and has a high average voltage. At the same capacity, its energy density is about 15% higher than that of lithium iron phosphate, so it has received widespread attention. However, the low electronic conductivity and ion transfer rate of lithium manganese iron phosphate limit its commercial application. In order to improve the above problems, carbon coating technology came into being. After carbon coating, lithium manganese iron phosphate has achieved significant results in improving its electronic conductivity and ion transfer rate.

[0003] However, the quality of the carbon layer coating lithium manganese iron phosphate is currently unstable, and the industry lacks quality control indicators for the carbon layer, which can easily lead to problems such as poor material capacity, low initial efficiency and poor long-cycle performance due to poor quality of the carbon layer. Summary of the invention

[0004] Based on this, the first aspect of the present application provides a positive electrode material, and its technical solution is as follows:

[0005] A positive electrode material comprises lithium iron manganese phosphate particles and a carbon coating layer coating the lithium iron manganese phosphate particles, wherein the chemical formula of the lithium iron manganese phosphate particles is LiMn x Fe y PO4, wherein x:y=(0.4~0.8):(0.2~0.6), the difference between the maximum and minimum thickness of the carbon coating layer is between 1nm~2nm; and the positive electrode material is distributed with pores, wherein the number of pores with a pore size exceeding 50nm accounts for 35%~50% of the total number of pores.

[0006] The second aspect of the present application provides a method for preparing a positive electrode material, and its technical solution is as follows:

[0007] A method for preparing a positive electrode material comprises the following steps:

[0008] According to the chemical formula LiMn x Fe y PO4 prepares manganese source, iron source, phosphorus source and lithium source, where x:y=(0.4~0.8):(0.2~0.6);

[0009] Mix the manganese source, iron source, phosphorus source, lithium source and carbon source to obtain a precursor solution, wherein the carbon source includes a viscosity of 8000mm at 25°C. 2 / s~17000mm 2 / s of polyacrylic acid;

[0010] Adjusting the particle size of solid particles in the precursor solution and then drying to obtain a precursor solid;

[0011] The precursor solid is subjected to microwave heating to obtain lithium iron manganese phosphate particles and a carbon coating layer coating the lithium iron manganese phosphate particles, wherein the difference between the maximum and minimum thicknesses of the carbon coating layer is between 1 nm and 2 nm; and the positive electrode material is distributed with pores, wherein the number of pores with a pore diameter exceeding 50 nm accounts for 35% to 50% of the total number of pores.

[0012] The third aspect of the present application provides a secondary battery, and its technical solution is as follows:

[0013] A secondary battery comprises the positive electrode material as described above.

[0014] Compared with the traditional solution, this application has the following beneficial effects:

[0015] This application combines experimental verification and finds that the thickness consistency of the carbon coating layer and the distribution of pores on the positive electrode material can be used as quality control indicators for the carbon layer coating lithium manganese iron phosphate particles, which has guiding significance for the key electrochemical properties of the positive electrode material. When the difference between the maximum and minimum thickness of the carbon layer is between 1nm and 2nm, and the number of pores with a pore size of more than 50nm in the positive electrode material accounts for 35% to 50% of the total number of pores, the positive electrode material has a higher compaction density and is conducive to the preparation of batteries with higher discharge capacity and first effect and good long cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0017] Figure 1 Schematic diagram of the principle of improving the solid solution effect of iron and manganese by polyacrylic acid;

[0018] Figure 2 is a SEM image of the positive electrode material of Example 1;

[0019] Figure 3 is the XRD pattern of the positive electrode material of Example 1;

[0020] Figure 4 This is the SEM image of the positive electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0021] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0023] the term

[0024] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0025] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0026] In the present application, “several” means at least one, such as one, two, etc., unless otherwise clearly defined.

[0027] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0028] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0029] In the present application, when referring to a numerical interval (i.e., a numerical range), unless otherwise specified, the optional numerical distribution within the above numerical interval is deemed to be continuous and includes the two numerical endpoints of the numerical range (i.e., the minimum value and the maximum value), and every numerical value between the two numerical endpoints.

[0030] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0031] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.

[0032] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0033] In the present application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.

[0034] The first aspect of the present application provides a positive electrode material. In one embodiment, the positive electrode material includes lithium iron manganese phosphate particles and a carbon coating layer coating the lithium iron manganese phosphate particles. The chemical formula of the lithium iron manganese phosphate particles is LiMn x Fe y PO4, wherein x:y=(0.4~0.8):(0.2~0.6), the difference between the maximum and minimum thickness of the carbon coating layer is between 1nm~2nm; and the positive electrode material is distributed with pores, wherein the number of pores with a pore diameter exceeding 50nm accounts for 35%~50% of the total number of pores.

[0035] The above implementation method is combined with experimental verification, and it is found that the thickness consistency of the carbon coating layer and the distribution of the pores of the positive electrode material can be used as quality control indicators of the carbon layer coating the lithium manganese iron phosphate particles, which has guiding significance for the key electrochemical properties of the positive electrode material. When the difference between the maximum and minimum thickness of the carbon layer is between 1nm and 2nm, and the number of pores with a pore size of more than 50nm in the positive electrode material accounts for 35% to 50% of the total number of pores, the positive electrode material has a higher compaction density and is conducive to the preparation of batteries with higher discharge capacity and first effect and good long cycle performance.

[0036] The percentage of the number of pores with a pore size of more than 50nm in the positive electrode material to the total number of pores can be measured by the nitrogen adsorption and desorption BJH determination method. During the test, the number of micropores, mesopores and macropores can be obtained by performing a BJH test on the positive electrode material sample, wherein the pore size of the micropores, mesopores and macropores satisfies: the pore size of the micropores ≤2nm, 2nm<the pore size of the mesopores ≤50nm, and the pore size of the macropores>50nm. Pores with a pore size of more than 50nm are macropores, and the total number of micropores, mesopores and macropores is the total number of pores. The percentage of the number of pores with a pore size of more than 50nm to the total number of pores can be obtained by calculation. It can be understood that the percentage of the number of pores with a pore size of more than 50nm in the positive electrode material to the total number of pores includes but is not limited to 35%, 40%, 45%, and 50%. After experimental verification, when the number of pores with a pore size of more than 50nm accounts for less than 35% of the total number of pores, the electrochemical performance of the battery is affected. The reason for this is that the number of macropores is small, resulting in low efficiency of lithium ion extraction and extraction of manganese phosphate. In addition, the number of macropores is small, and many micropores and mesopores inside cannot be exposed and cannot play a role, affecting the material's cycle performance. When the number of pores with a pore size of more than 50nm accounts for more than 50% of the total number of pores, the electrochemical performance of the battery is also affected. The reason for this is that the number of macropores is large, resulting in a low compaction density of the positive electrode sheet.

[0037] In traditional lithium iron manganese phosphate positive electrode materials, the solid solution effect of iron and manganese is poor, and iron oxide and manganese pyrophosphate impurities are easily present, affecting the electrochemical performance of the battery. In the above-mentioned positive electrode materials, by selecting the carbon source of the positive electrode material, the solid solution effect of iron and manganese can be improved, and the appearance of iron oxide and manganese pyrophosphate impurities can be avoided. The chemical formula of manganese pyrophosphate is Mn2P2O7. Optionally, the carbon source of the positive electrode material includes polyacrylic acid, which has a carboxyl group. The presence of the carboxyl group can complex manganese ions and iron ions, improve the solid solution effect of iron and manganese, and further limit the viscosity range to a viscosity of 8000mm at 25°C. 2 / s~17000mm 2 / s of polyacrylic acid decomposes at high temperature and in-situ coats the lithium iron manganese phosphate primary particles at the complexing position to form a relatively uniform carbon coating layer, avoiding the presence of iron oxide and manganese pyrophosphate impurities. Optionally, the positive electrode material does not contain iron oxide and the positive electrode material does not contain manganese pyrophosphate. Not containing iron oxide and / or not containing manganese pyrophosphate helps to improve the efficiency of lithium ion deintercalation and improve electrochemical performance.

[0038] Among them, the thickness of the carbon coating layer can be obtained by dissecting the primary particles of the positive electrode material with a focused ion beam technique, and then performing a TEM test to observe and measure the thickness of the carbon coating layer and calculate the average value. The difference between the maximum and minimum thickness of the carbon coating layer is between 1nm and 2nm, indicating that the carbon coating layer can evenly coat the lithium iron manganese phosphate particles and the product consistency is good. Optionally, the average thickness of the carbon coating layer is 2nm to 4nm. If the carbon layer is too thin, the material coating is incomplete, which affects the cycle performance. If the carbon layer is too thick, it affects the insertion and removal of lithium ions, the charging and discharging of the material is incomplete, and the first efficiency is low. It can be understood that the average thickness of the carbon coating layer includes but is not limited to 2nm, 3nm, and 4nm.

[0039] Optionally, the primary particle size of the positive electrode material is between 150nm and 400nm. It should be noted that the positive electrode material is a secondary particle composed of primary particles, and the primary particle size of the positive electrode material is between 150nm and 400nm, which can effectively reduce the agglomeration of primary particles in the secondary particles, so that the primary particles in the secondary particles are in a more uniform state. The agglomeration of primary particles will cause the lithium ion diffusion path to become longer, affecting the cycle performance of the material.

[0040] A second aspect of the present application provides a method for preparing a positive electrode material. In one embodiment, the method for preparing a positive electrode material comprises the following steps:

[0041] S10, by chemical formula LiMn x Fe y PO4 prepares manganese source, iron source, phosphorus source and lithium source, where x:y=(0.4~0.8):(0.2~0.6);

[0042] Optionally, the manganese source comprises manganese oxide.

[0043] Optionally, the iron source comprises iron oxide.

[0044] Optionally, the phosphorus source includes at least one of phosphoric acid, lithium dihydrogen phosphate and ammonium dihydrogen phosphate.

[0045] Optionally, the lithium source includes at least one of lithium carbonate and lithium dihydrogen phosphate.

[0046] In some examples, the molar ratio of lithium (Li) to phosphorus (P) in the lithium source and the phosphorus source is controlled to be (1.01-1.04):1.

[0047] S20, mixing the manganese source, iron source, phosphorus source, lithium source and carbon source to obtain a precursor solution, wherein the carbon source includes a viscosity of 8000mm at 25°C. 2 / s~17000mm 2 / s of polyacrylic acid;

[0048] The above preparation method is based on a viscosity of 8000mm at 25°C. 2 / s~17000mm 2 / s of polyacrylic acid as a carbon source. On the one hand, see Figure 1 , which shows a schematic diagram of the principle of polyacrylic acid improving the solid solution effect of iron and manganese. After polyacrylic acid is mixed with manganese source and iron source in the raw material mixing stage, the carboxyl group of polyacrylic acid is used to complex iron ions and manganese ions to improve the solid solution effect of iron and manganese, and manganese and iron are mixed evenly, which is beneficial to improve the efficiency of lithium ion deintercalation and electrochemical performance. At the same time, polyacrylic acid within the viscosity range decomposes at high temperature and in-situ coats the primary particles of lithium iron manganese phosphate at the complexing position to form a relatively uniform carbon coating layer, avoiding the presence of iron oxide and manganese pyrophosphate impurities during the preparation process, improving the electronic conductivity and ion transfer rate of lithium iron manganese phosphate positive electrode materials, and improving the problems of poor capacity, low first efficiency and poor long cycle performance of positive electrode materials. On the other hand, lithium iron manganese phosphate generally does not have a good affinity with carbon, so the carbon coating effect of lithium iron manganese phosphate is average. In addition, acrylic acid is a vinyl-containing monomer that is very easy to polymerize. When the temperature exceeds 100°C, it will rapidly self-polymerize. Experimental data show that if the chain length of polyacrylic acid is too long and the viscosity is high at 25°C, the carbon coating layer formed subsequently is easy to fall off from the primary particles of lithium manganese iron phosphate, resulting in uneven coating, and even leaving part of the lithium manganese iron phosphate exposed to the outside, affecting the electrochemical performance of the positive electrode material. This embodiment attempts to add an inhibitor during the polymerization of polyacrylic acid to stabilize its performance and block the polymerization reaction in time (because the polymerization reaction requires free radicals to initiate a chain reaction, and the inhibitor can react with free radicals to reduce the concentration of free radicals, and quench the free radicals under the action of oxygen to form peroxides to terminate the polymerization reaction), generate short-chain polyacrylic acid, and make its viscosity at 25°C 8000mm 2 / s~17000mm 2 / s, experimental data show that the carbon coating formed by short-chain polyacrylic acid has good coating uniformity on lithium manganese iron phosphate, and the difference between the maximum and minimum thickness of the carbon coating is between 1nm and 2nm, which is not easy to fall off. At the same time, it has been verified through experiments that the length of the polyacrylic acid chain has an impact on the proportion of macropores in the final positive electrode material. Using the viscosity of 8000mm at 25°C 2 / s~17000mm 2 / s polyacrylic acid as a carbon source can control the number of pores with a pore size of more than 50nm on the positive electrode material to account for 35% to 50% of the total number of pores. At this time, the positive electrode material has a higher compaction density and is conducive to preparing a battery with higher discharge capacity and first efficiency and good long cycle performance. Optionally, the preparation method of polyacrylic acid includes the following steps:

[0049] Mix the acrylic acid monomer and the polymerization inhibitor, heat and polymerize until the viscosity at 25°C is 8000 mm 2 / s~17000mm 2 / s of polyacrylic acid.

[0050] The viscosity of polyacrylic acid can reflect the size of the molecular weight, and then reflect the length of the polyacrylic acid chain. The molecular weight can be measured by Ubbelohde viscometer. According to the formula [η] = KM α (K and α are constants, M is the molecular weight, K is the proportional constant, which is greatly affected by temperature, and α is the degree of stretching of the polymer coil in a certain solvent at a certain temperature, with a value between 0.5 and 1) to obtain the viscosity. The viscous flow of polymers is the result of the displacement of the center of gravity of the molecular chain along the flow direction and the mutual slippage between chains. The larger the molecular weight, the more segments a molecular chain contains. In order to achieve the migration of the center of gravity, the more times the synergistic effects of the segments need to be completed. Therefore, the shear viscosity of the polymer melt increases with the increase of molecular weight. The larger the molecular weight, the poorer the fluidity and the higher the apparent viscosity. Moreover, the slow increase in molecular weight will cause a sharp increase in apparent viscosity. The kinematic viscosity ranges from 7000mm² / s to 180000mm² / s.

[0051] The polyacrylic acid after adding the inhibitor has better adaptability and fluidity, can better coat the primary particles of lithium iron manganese phosphate, and has less agglomeration. Optionally, the inhibitor includes one of 4-methoxyphenol, hydroquinone and p-hydroxyanisole, and preferably, the inhibitor includes 4-methoxyphenol. 4-methoxyphenol can be mild and easily decomposed. In addition, 4-methoxyphenol can generate carboxyl groups under an oxygen atmosphere, which can further complex manganese and iron ions in the raw material mixing stage, increase the solid solubility of manganese and iron, and thus improve the electrochemical performance of the positive electrode material.

[0052] Optionally, the polymerization reaction temperature is 40° C. to 60° C. At this polymerization reaction temperature, acrylic acid is not prone to rapid self-polymerization.

[0053] Optionally, the polymerization reaction time is 20 min to 40 min.

[0054] Optionally, the carbon source mass is similar to LiMn x Fe y The mass ratio of PO4 is (0.03-0.07):1. At this time, the average thickness of the carbon coating layer is 2nm-4nm.

[0055] S30, adjusting the particle size of the solid particles in the precursor solution and then drying to obtain a precursor solid;

[0056] The precursor solution may be ground in a coarse grinder and a sand mill to adjust the particle size of the solid particles in the precursor solution. Optionally, the average particle size of the solid particles in the precursor solution is adjusted to 100 nm to 300 nm.

[0057] The drying method may be spray drying.

[0058] S40. The precursor solid is subjected to microwave heating to obtain lithium iron manganese phosphate particles and a carbon coating layer coating the lithium iron manganese phosphate particles, wherein the difference between the maximum and minimum thickness of the carbon coating layer is between 1 nm and 2 nm; and the positive electrode material is distributed with pores, wherein the number of pores with a pore diameter exceeding 50 nm accounts for 35% to 50% of the total number of pores.

[0059] Optionally, microwave heating includes the following procedures:

[0060] Keep the temperature at 550℃~650℃ and nitrogen atmosphere for 20min~30min. Microwave heating has low temperature, low energy consumption, short heating time and high efficiency.

[0061] During the microwave heating process, polyacrylic acid decomposes and in-situ coats the lithium manganese iron phosphate primary particles at the complexing position to form a relatively uniform carbon coating layer, and the inhibitor decomposes.

[0062] The preparation method uses the early complexation of polyacrylic acid to make manganese ions and iron ions fully contact and evenly distribute at the microscopic level, with good mixing effect, which is conducive to the uniform phase of the product. At the same time, a carbon coating layer is formed in situ, the thickness of the carbon coating layer is uniform, and the carbon coating layer is not easy to fall off when in contact with lithium manganese iron phosphate, and the number of pores with a pore diameter of more than 50nm on the positive electrode material can be controlled to account for 35% to 50% of the total number of pores. At this time, the positive electrode material has a higher compaction density and is conducive to the preparation of batteries with higher discharge capacity and first effect and good long cycle performance. At the same time, the particle size distribution range of the positive electrode material is narrow, and the product consistency is good.

[0063] A third aspect of the present application provides a secondary battery. In one embodiment, the secondary battery includes the positive electrode material as described above.

[0064] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0065] Example 1

[0066] This embodiment provides a positive electrode material and a preparation method thereof, the steps are as follows:

[0067] (1) Acrylic acid monomer and 0.06% by weight of 4-methoxyphenol were stirred and mixed, heated to 50°C, reacted for 30 minutes and then stopped stirring to prepare polyacrylic acid. The viscosity of the polyacrylic acid at 25°C was measured by an Ubbelohde viscometer to be 12000 mm² / s.

[0068] (2) According to the chemical formula LiMn 0.6 Fe 0.4 PO4: Add ferromanganese oxide and industrial grade phosphoric acid into a certain amount of deionized water and stir evenly to fully dissolve them.

[0069] (3) According to the chemical formula LiMn 0.6 Fe 0.4 Slowly add industrial grade lithium carbonate to the solution in step (2) to prevent splashing, stir for 30 minutes, and then add the theoretically obtained LiMn 0.6 Fe 0.4 5% polyacrylic acid by mass of PO4 is added to fully dissolve all raw materials to obtain a precursor solution.

[0070] (4) Transfer the precursor solution to a coarse grinder, adjust the speed to 1500 r / min, and coarse grind for one hour.

[0071] (5) The coarsely ground slurry was transferred to a sand mill and the speed was adjusted to 1500 r / min. The slurry was sand milled for half an hour. When the average particle size of the solid particles was 200 nm, the slurry was discharged and transferred to spray drying.

[0072] (6) The spray outlet temperature was set to 95 °C and spray drying was performed to obtain a precursor solid.

[0073] (7) The precursor solid of step (6) was transferred to a microwave oven, nitrogen was introduced, the temperature was adjusted to 600°C, and the temperature was kept at this temperature for 25 minutes to obtain a positive electrode material.

[0074] The SEM image of the positive electrode material of this embodiment is as follows Figure 2 As shown, SEM observed that the primary particle size was between 150nm and 400nm. The primary particles of the positive electrode material were dissected using focused ion beam technology, and then TEM was performed to observe and measure the thickness of the carbon coating layer on various aspects of the primary particles. The average thickness was 3nm, and the difference between the maximum and minimum values ​​was between 1nm and 2nm, indicating that a carbon coating layer of uniform thickness was formed on the surface of the lithium manganese iron phosphate primary particles. The number of pores exceeding 50nm was determined by nitrogen adsorption and desorption BJH, accounting for 45% of the total number of pores. The above test results are summarized in Table 1.

[0075] The XRD pattern of the positive electrode material in this embodiment is as follows Figure 3 As shown, it can be seen that there is no iron oxide and manganese pyrophosphate in the positive electrode material.

[0076] Example 2

[0077] This embodiment provides a positive electrode material and a preparation method thereof, which are basically the same as those of Embodiment 1, except that: in step (1), 0.08% of 4-methoxyphenol by weight of the acrylic acid monomer is added and stirred to prepare polyacrylic acid with a viscosity of 8000 mm² / s at 25°C.

[0078] SEM observations showed that the primary particle size of the obtained positive electrode material was between 150nm and 400nm. The primary particles of the positive electrode material were dissected using focused ion beam technology, and then TEM was performed to observe and measure the thickness of the carbon coating layer on various aspects of the primary particles. The average thickness was 3nm, and the difference between the maximum and minimum values ​​was between 1nm and 2nm. The number of pores exceeding 50nm was determined by nitrogen adsorption and desorption BJH to account for 38% of the total number of pores. XRD measurements showed that there was no iron oxide and manganese pyrophosphate in the positive electrode material.

[0079] Example 3

[0080] This embodiment provides a positive electrode material and a preparation method thereof, which are basically the same as those of Embodiment 1, except that: in step (1), 0.01% of 4-methoxyphenol by weight of the acrylic acid monomer is added and stirred to prepare polyacrylic acid with a viscosity of 17000 mm² / s at 25°C.

[0081] SEM observations showed that the primary particle size of the obtained positive electrode material was between 150nm and 400nm. The primary particles of the positive electrode material were dissected using focused ion beam technology, and then TEM was performed to observe and measure the thickness of the carbon coating layer on various aspects of the primary particles. The average thickness was 3nm, and the difference between the maximum and minimum values ​​was between 1nm and 2nm. The number of pores exceeding 50nm was determined by nitrogen adsorption and desorption BJH, accounting for 47% of the total number of pores. XRD measurements showed that there was no iron oxide and manganese pyrophosphate in the positive electrode material.

[0082] Example 4

[0083] This embodiment provides a positive electrode material and a preparation method thereof, which is basically the same as that of Embodiment 1, except that in step (3), the amount of carbon source used is different. Step (3) is specifically as follows:

[0084] (3) According to the chemical formula LiMn 0.6 Fe 0.4 Slowly add industrial grade lithium carbonate to the solution in step (2) to prevent splashing, stir for 30 minutes, and then add the theoretically obtained LiMn 0.6 Fe 0.4 7% polyacrylic acid by mass of PO4 is added to fully dissolve all raw materials to obtain a precursor solution.

[0085] SEM observations showed that the primary particle size of the obtained positive electrode material was between 150nm and 400nm. The primary particles of the positive electrode material were dissected using focused ion beam technology, and then TEM was performed to observe and measure the thickness of the carbon coating layer on various aspects of the primary particles. The average thickness was 4nm, and the difference between the maximum and minimum values ​​was between 1nm and 2nm. The number of pores exceeding 50nm was determined by nitrogen adsorption and desorption BJH to account for 42% of the total number of pores. XRD measurements showed that there was no iron oxide and manganese pyrophosphate in the positive electrode material.

[0086] Example 5

[0087] This embodiment provides a positive electrode material and a preparation method thereof, which is basically the same as that of Embodiment 1, except that step (5) is different. Step (5) is specifically as follows:

[0088] (5) The coarsely ground slurry was transferred to a sand mill and the speed was adjusted to 1500 r / min. The slurry was sand milled for 1 hour. When the average particle size of the solid particles was 120 nm, the slurry was discharged and transferred to spray drying.

[0089] SEM observations showed that the primary particle size of the obtained positive electrode material was between 100nm and 200nm. The primary particles of the positive electrode material were dissected using focused ion beam technology, and then TEM was performed to observe and measure the thickness of the carbon coating layer on various aspects of the primary particles. The average thickness was 3nm, and the difference between the maximum and minimum values ​​was between 1nm and 2nm. The number of pores exceeding 50nm was determined by nitrogen adsorption and desorption BJH, accounting for 40% of the total number of pores. XRD measurements showed that there was no iron oxide and manganese pyrophosphate in the positive electrode material.

[0090] Example 6

[0091] This embodiment provides a positive electrode material and a preparation method thereof, which are basically the same as those in Embodiment 1, except that: This embodiment provides a positive electrode material and a preparation method thereof, which are basically the same as those in Embodiment 1, except that: in step (3), the amount of carbon source used is different. Step (3) is specifically as follows:

[0092] (3) According to the chemical formula LiMn 0.6 Fe 0.4 Slowly add industrial grade lithium carbonate to the solution in step (2) to prevent splashing, stir for 30 minutes, and then add the theoretically obtained LiMn 0.6 Fe 0.4 9% polyacrylic acid by mass of PO4 is added to fully dissolve all raw materials to obtain a precursor solution.

[0093] SEM observations showed that the primary particle size of the obtained positive electrode material was between 150nm and 400nm. The primary particles of the positive electrode material were dissected using focused ion beam technology, and then TEM was performed to observe and measure the thickness of the carbon coating layer on various aspects of the primary particles. The average thickness was 5nm, and the difference between the maximum and minimum values ​​was between 1nm and 2nm. The number of pores exceeding 50nm was determined by nitrogen adsorption and desorption BJH, accounting for 35% of the total number of pores. XRD measurements showed that there was no iron oxide and manganese pyrophosphate in the positive electrode material.

[0094] The primary particle size of the positive electrode materials of Examples 1-6, the average thickness of the carbon coating layer, the difference between the maximum and minimum thickness of the carbon coating layer, the ratio of the number of pores with a pore size of more than 50 nm to the total number of pores determined by BJH, and the results of XRD determination of whether iron oxide and manganese pyrophosphate are contained are summarized in Table 1.

[0095] Table 1

[0096]

[0097] Comparative Example 1

[0098] This comparative example provides a positive electrode material and a preparation method thereof, which are basically the same as those of Example 1, except that: in step (1), no 4-methoxyphenol is added to prepare polyacrylic acid with a viscosity of 50,000 mm² / s at 25°C.

[0099] The nitrogen adsorption-desorption BJH analysis showed that the number of pores larger than 50 nm accounted for 53% of the total number of pores. XRD analysis showed that the positive electrode material contained iron oxide and manganese pyrophosphate.

[0100] The SEM image of the positive electrode material of this comparative example is as follows Figure 4 As shown, Figure 4 It shows that the number of pores larger than 50 nm accounts for a large proportion, and the carbon coating is uneven. The growth of lithium manganese iron phosphate particles is not restricted, and the particle size varies greatly.

[0101] Comparative Example 2

[0102] This comparative example provides a positive electrode material and a preparation method thereof, which are basically the same as those of Example 1, except that in step (1), polyacrylic acid with a viscosity of 5000 mm² / s at 25°C is prepared.

[0103] The nitrogen adsorption-desorption BJH analysis showed that the number of pores larger than 50 nm accounted for 31% of the total number of pores. XRD analysis showed that the positive electrode material contained iron oxide and manganese pyrophosphate.

[0104] Electrochemical performance test

[0105] The positive electrode materials of the above-mentioned embodiments and comparative examples were assembled into button cells and soft-pack cells, and their electrochemical properties were tested. The assembly steps and testing methods are as follows:

[0106] LMFP, SP, KS-6 and dispersant were mixed in a mass ratio of 95:2.2:0.4:0.2:2.2 to prepare positive electrode slurry, which was coated on a carbon-coated aluminum foil current collector to obtain a positive electrode sheet. Graphite, CMC, SP and SBR were mixed in a mass ratio of 95.50:1.50:1:2 to prepare negative electrode slurry, which was coated on a copper foil current collector to obtain a negative electrode sheet. PP+PE+PP was used as a separator and C48 was used as an electrolyte to assemble a soft pack battery to test the cycle performance.

[0107] The test results are shown in Table 2.

[0108] Table 2

[0109]

[0110] As can be seen from Table 1, when the number of pores with a pore size of more than 50 nm on the positive electrode material accounts for 35% to 50% of the total number of pores, the positive electrode material has a higher compaction density and is conducive to the preparation of batteries with higher discharge capacity and first effect and good long cycle performance. In Comparative Example 1, the number of pores exceeding 50 nm accounts for a large proportion, the compaction density is low, and the carbon coating layer and the primary particles of lithium manganese iron phosphate fall off, the coating is uneven, and the electrochemical performance is poor. In Comparative Example 2, the number of pores exceeding 50 nm accounts for a small proportion, the efficiency of lithium ion insertion and extraction of manganese phosphate is low, and the electrochemical performance is poor.

[0111] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0112] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: According to the chemical formula LiMn x Fe y PO4 prepares manganese source, iron source, phosphorus source and lithium source, where x:y=(0.4~0.8):(0.2~0.6); Mix the manganese source, iron source, phosphorus source, lithium source and carbon source to obtain a precursor solution, wherein the carbon source includes a viscosity of 8000mm at 25°C. 2 / s~17000mm 2 / s of polyacrylic acid; Adjusting the particle size of solid particles in the precursor solution and then drying to obtain a precursor solid; The precursor solid is subjected to microwave heating to obtain lithium iron manganese phosphate particles and a carbon coating layer coating the lithium iron manganese phosphate particles, wherein the difference between the maximum and minimum thicknesses of the carbon coating layer is between 1 nm and 2 nm; and the positive electrode material is distributed with pores, wherein the number of pores with a pore diameter exceeding 50 nm accounts for 35% to 50% of the total number of pores.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: The carbon source mass and LiMn x Fe y The mass ratio of PO4 is (0.03~0.07):

1.

3. The method for preparing a positive electrode material according to any one of claims 1 to 2, characterized in that: The preparation method of the polyacrylic acid comprises the following steps: Mix the acrylic acid monomer and the polymerization inhibitor, heat and polymerize until the viscosity at 25°C is 8000 mm 2 / s~17000mm 2 / s of polyacrylic acid.

4. The method for preparing the positive electrode material according to claim 3, characterized in that: Includes at least one of the following features: (1) The inhibitor includes 4-methoxyphenol; (2) The polymerization reaction temperature is 40°C to 60°C; (3) The polymerization reaction time is 20 min to 40 min.

5. The method for preparing a positive electrode material according to any one of claims 1 to 2 and 4, characterized in that: Includes at least one of the following features: (1) The manganese source includes manganese oxide; (2) The iron source comprises iron oxide; (3) The phosphorus source includes at least one of phosphoric acid, lithium dihydrogen phosphate and ammonium dihydrogen phosphate; (4) The lithium source includes at least one of lithium carbonate and lithium dihydrogen phosphate; (5) The microwave heating comprises the following procedures: keeping the temperature at 550°C to 650°C and in a nitrogen atmosphere for 20 min to 30 min; (6) Adjusting the particle size of the solid particles in the precursor solution to 100 nm to 300 nm.

6. A positive electrode material, prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The positive electrode material comprises lithium iron manganese phosphate particles and a carbon coating layer coating the lithium iron manganese phosphate particles, wherein the chemical formula of the lithium iron manganese phosphate particles is LiMn x Fe y PO4, wherein x:y=(0.4~0.8):(0.2~0.6), the difference between the maximum and minimum thickness of the carbon coating layer is between 1nm~2nm; and the positive electrode material is distributed with pores, wherein the number of pores with a pore size exceeding 50nm accounts for 35%~50% of the total number of pores.

7. The positive electrode material according to claim 6, characterized in that The positive electrode material includes at least one of the following features: (1) The positive electrode material does not contain iron oxide; (2) The positive electrode material does not contain manganese pyrophosphate.

8. The positive electrode material according to any one of claims 6 to 7, characterized in that The average thickness of the carbon coating layer is 2nm~4nm.

9. The positive electrode material according to any one of claims 6 to 7, characterized in that The primary particle size of the positive electrode material is between 150nm and 400nm.

10. A secondary battery, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Method for producing lithium manganese iron phosphate particulate powder, lithium manganese iron phosphate particulate powder and non-aqueous electrolyte secondary battery using that particulate powder

    CN102781827A

  • Method for Preparation of Olivine Type Lithium Manganese Iron Phosphate and Product Obtained from the Same

    KR1020150120910A